Cover Image. Issue 23 (30th November 2021) - Unknown
Abstract : Cover Illustrations: (Left to Right): (Image 1): A model to promote and sustain high‐quality biodiversity tissue archives. See Blom, 2021 in Special Issue for further details; (Image 2): Clockwise from top left are examples of a deletion, insertion, tandem duplication, chromosomal translocation and an inversion; (Image 3): Diagram showing the distribution of sequencing reads mapped to a reference genome under (A) a RAD‐seq, (B) a Pool‐seq, and (C) a lcWGS design; (Image 4): Male Audubon's yellow‐rumped warbler (Setophaga coronata auduboni); (Image 5): Male hihi on the lookout, captured in Zealandia, Wellington (Aotearoa New Zealand); (Image 6): Optimizing the assembly and loci extraction from different types of sequencing techniques is a way forward for phylogenomics and molecular ecology, especially for non‐model organisms such as the specimen from the Urbanus genus (Lepidoptera: Hosperiidae) seen in the photo; (Image 7): To estimate de novo mutation rates in sexually reproducing organisms, investigators can compare the genomes of parents and their offspring (so‐called 'trio' studies) to count mutations that have occurred in the parental germline. These mutations provide fuel for the engine of evolution; (Image 8): The African golden wolf is very well adapted to various types of habitats, including very dry areas. The image was taken in the Atlas Mountains; (Image 9): Curious caribou, Sahtu mountains; (Image 10): Ancient DNA recovered from fosssils reveals that ancient horses (Equus caballus) spanned the Beringia region during the ice age; (Image 11): whole genome sequences of killer whales reveal demographic histories; (Image 12): Loggerhead (Caretta caretta) sea turtle; (Image 13): Zaprionus spp. in the field on the island of São Tomé; (Image 14): Lab colony of the ant Cardiocondyla obscurior; (Image 15): Helianthus annuus subsp. texanus inflorescence; (Image 16): A Formica obscuripes worker in the Cascade Mountains, Washington, USA; (Image 17): The European cherry fruit fly Rhagoletis cerasi is an important economic pest species infesting cherries in its native range in Europe; (Image 18): Bighorn sheep (Ovis canadensis) photo taken at Banff National Park, CA; (Image 19): The invasion sequence: a longstanding eco‐evolutionary model of biological invasion; (Image 20): Adult Komodo dragon Varanus komodoensis; (Image 21): Chelonoidis duncanensis adult in the wild on PinzÓn Island, Galapagos; (Image 22): A male Mexican wolf at Wolf Conservation Center; (Image 23): A close‐up image of a southern white rhinoceros at the Manyeleti Game Reserve, South Africa. Taken in March 2020; (Image 24): Kea (Nestor notabilis) on the Te Anau‐Milford Sound road, in Southland, New Zealand; (Image 25): Heliconius erato lativitta; (Image 26): Experimental population of the copepod Tigriopus californicus; (Image 27): Three adult acorn barnacles (Semibalanus balanoides) in the swedish rocky shore; (Image 28): Indo‐Pacific bottlenose dolphins (Tursiops aduncus) in Gulf St Vincent, South Australia; (Image 29): Phyllostomus discolor; (Image 30): Graphs showing genome‐wide associations between SNP variants and environmental variables for Anopheles gambiae, with genetic sampling points shown on a map of continent‐wide precipitation. Inset photo of a female Anopheles gambiae individual obtaining a blood meal accessed from the Center for Disease Control Public Health Image Library; (Image 31): Annual population of the common monkeyflower, Mimulus guttatus, in bloom in the Cascades Range near the high elevation end of the transect sampled for population re‐sequencing by Colicchio et al. in this issue. Photo Credit: (Left to Right): (Image 1): Dr. Foteini Spagopoulou; (Image 2): Illustrated by Jana Wold; (Image 3): not a photograph, but Arne Jacobs and Nina O. Therkildsen made the figure; (Image 4): Sheri Rypstra; (Image 5): Stuart Attwood; (Image 6): Daniel Linke; (Image 7): David Haring, Duke Lemur Center; (Image 8): Vicente Urios; (Image 9): Pierre‐Emmanuel Chaillon; (Image 10): Julius Csotonyi; (Image 11): Andrew Foote; (Image 12): TAMAR Image Bank; (Image 13): Aaron Comeault; (Image 14): Mohammed Errbii; (Image 15): Nora Mitchell; (Image 16): Daniel K. Pierce; (Image 17): Hannes Schuler; (Image 18): Sarah H. D. Santos; (Image 19): Henry North; (Image 20): Achmad Ariefiandy; (Image 21): Evelyn Jensen; (Image 22): Wolf Conservation Center; (Image 23): Yoshan Moodley; (Image 24): Federico Massetti; (Image 25): Dr Luca Livraghi; (Image 26): Ana Luisa Ahern; (Image 27): Fredrik Pleijel; (Image 28): Nikki Zanardo; (Image 29): Stephen J. Rossiter; (Image 30): CDC/James Gathany; (Image 31): Benjamin K. Blackman.